2005
DOI: 10.2134/agronj2005.0219a
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins Produced by Fusarium spp. in Isogenic Bt vs. non‐Bt Maize Hybrids under European Corn Borer Pressure

Abstract: Stalk and ear rots caused by Fusarium subspecies are often related to mycotoxin accumulation in maize (Zea mays L.) kernels. Various mycotoxicoses in livestock and humans are triggered by the consumption of these toxins. The European corn borer (Ostrinia nubilalis Hübner) reportedly promotes the infection by Fusarium spp. The objectives of our study were to (i) evaluate the concentration of deoxinivalenol (DON), 3‐acetyl‐deoxynivalenol (3‐A‐DON), 15‐acetyl‐deoxynivalenol (15‐A‐DON), fumonisin (FUM), fusarenon‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For five locations, the significant differences between cob damage were equal to 17.7% for GM versus non-Bt cultivars (Table 6). It was well established that maize cobs injured by ECB are always infected by pathogenic fungi, contaminating kernels with mycotoxins (Papst et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…For five locations, the significant differences between cob damage were equal to 17.7% for GM versus non-Bt cultivars (Table 6). It was well established that maize cobs injured by ECB are always infected by pathogenic fungi, contaminating kernels with mycotoxins (Papst et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Reid et al [23] found only a few genotypes that were good for both resistance types. Despite the positive opinion on the role of silk in the infection process, spraying the silks (GER) was not successful [56]. The silk channel infection achieved better results, but exhibited a lower infection severity compared with the kernel resistance test.…”
Section: Discussionmentioning
confidence: 99%
“…Methods that have been suggested for the control of ECB population and damage include the planting of genetically engineered corn hybrids, tolerant hybrids [18], crop techniques such as shredding and ploughing, and chemical treatment by means of selfpowered spraying machines applying organophosphates and pyrethroids [19][20][21]. In SEE conventional corn production, chemical methods represent the main strategy for controlling ECB damage.…”
Section: Introductionmentioning
confidence: 99%